Does Confucius have a say in management today? Empirical evidence from Asia and Europe. (29th January 2022) - Vaszkun, Balázs; Koczkás, Sára; Ganbaatar, Tseren; Chi-Hsien, Kuo; Yu, Yanghang; Yao, Yuan; Sárvári, Balázs; Orolmaa, Munkhbat
The aim of this paper is to assess whether Confucianism impacts the personality and behaviour of Chinese managers. We made a comparison between the findings of existing literature on Confucian management, the concepts of the Analects concerning leadership, and the results of empirical data collected from 30 participants. Data obtained from Chinese managers was compared with that from a control group consisting of managers of European and Asian origin. The methodology and findings enabled us to discover subtle differences between the concepts of Confucianism, as formulated in the Analects, and Chinese and Western business leaders' management practices.